Channeling identification: How perceived regulatory focus moderates the influence of organizational and professional identification on professional employees' diagnosis and treatment behaviors. (March 2016) - Hekman, David R; van Knippenberg, Daan; Pratt, Michael G
We suggest that organizational and professional identification are two sources of motivation that can be channeled in similar or different directions based on perceived organizational and professional regulatory focus. Specifically, we hypothesize and find that both types of identification-based motivation are channeled toward diagnosis behaviors when professionals think their coworkers and colleagues value a promotion focus, and they are channeled toward treatment behaviors when professionals think their coworkers and colleagues value a prevention focus. Our results advance research on social identification by helping to explain how and when organizational and professional identification influence work performance, and also advance the organizational literature on professions by introducing diagnosis and treatment as two theory-derived types of in-role performance for professional employees.